Synthesis and Medical Application of 3D Graphene Materials - Terver John Sase; Karniliyus Emmanuel Daring; Yilni Edward Bioltif (Indonesian Journal of Multidisciplinary Science, 2023)
3D graphene materials are carbon nanomaterials that are gaining significant attention recently due to their unique properties. They are incredibly strong, have unique electrical, thermal optical and chemical properties that make them stand out and are the preferred materials of choice in the material sciences. These unique materials have gained significant attention since 2004 and have now been used for various applications including medical uses. In this review, we explored some recent advances in the research of these unique materials, their synthesis methods and their several medical applications. Several synthesis techniques are being developed to be able to improve the synthesis of this material within a short or less time maintaining the structure and its unique properties. These unique properties that this special material possesses have been harnessed and utilized for application in so many areas such as agriculture, energy, water purification including biomedical applications as discussed.